Aesthetic and functional rehabilitation of anterior teeth after trauma: a case report - Scudine, Kelly Guedes de Oliveira; Moreira, Kelly Maria Silva; Cardoso, Micaela; Araújo, Stéphanie Marani Martins; Puppin-Rontani, Regina Maria; Santos, Eduardo César Almada (Clinical and Laboratorial Research in Dentistry, 2018)
Traumatic dental injuries are common clinical problems during childhood, and may have complex etiologies causing physical and physiological impairment. The aim of this study was to report the management of a severe traumatic dental injury in an 8-year-old female patient, victim of a motorcycle accident, who was taken to a pediatric dentistry clinic three months after the accident. After clinical and radiografic examination, we observed the avulsion of the permanent maxillary central incisors and of the permanent left lateral incisor, with considerable lingual interposition, interfering in speech and swallowing. The patient showed low risk of caries and good behavior during the appointments. However, she demonstrated to be embarrassed to smile. Besides the preventive treatment concerning caries, the treatment plan included immediate care and subsequent monitoring of the psychosocial reestablishment. For this purpose, an acrylic partial denture was made in order to replace the missing anterior teeth, maintaining the characteristics of the mixed dentition and preserving the aesthetics and the function. Follow-up appointments were performed one, three and six months after the first visit, aiming to monitor the adaptation of the prosthesis, as well as the growth and development of the child’s dentition. Thus, the aesthetic and functional rehabilitation was achieved regarding the patient’s satisfaction, enabling immediate social reinsertion.